Understanding myocardial infarction trends during the early COVID‐19 pandemic: an infodemiology study. Issue 8 (2nd July 2021) - Dzaye, Omar; Duebgen, Matthias; Berning, Philipp; Graham, Garth; Martin, Seth S.; Blaha, Michael J.
Abstract: During the first months of the coronavirus disease 2019 (COVID‐19) pandemic in early 2020, Google Trends data in the United States showed a strong increase in search query frequency for chest pain symptoms despite a concurrent decrease in search interest for myocardial infarction. This suggests a reduced attention to acute coronary syndrome (ACS) and chest pain as its main symptom during this time period. These observations could help explain why cardiovascular mortality rose dramatically despite a strong decrease in hospitalisation rates for ACS.